On Certain Series to Series Transformation and Analytic Continuations by Matrix Methods - Sahani, Suresh Kumar; Paudel, Gyan Prasad; Ghimire, Jhavi Lal; Thakur, Amarnath Kumar (Nepal Journal of Mathematical Sciences, 2022)
In this research paper, we proved some general theorems on the absolute convergence transformation of matrix which is expressed in terms of preserving transformation under the very general conditions. This works is motivated by the works of [3],[12] and [14].